Life on the Edge : A Young Adult's Guide to a Meaningful Future - James Dobson 1936- (Dallas : Word Publishing, 1995)
Provides scriptural foundations on which high school seniors can base crucial decisions about their future lives
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Theology -- Life change events -- Psychological aspects; Life change events -- Religious aspects -- Christianity; Teenagers -- Conduct of life; Young adults -- Conduct of life; Teenagers -- Religious life; Young adults -- Religious life